![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\dfrac{5^2\cdot6\cdot\left(-16\right)^2+6^2\left(-12\right)^6\left(-15\right)^2}{2\left(-6\right)\cdot2\cdot10^4-81^2\cdot960^3}=\dfrac{3\cdot5^2\cdot2^9+2^{14}\cdot3^{10}\cdot5^2}{-2^7\cdot3\cdot5^4-2^{18}\cdot3^{11}\cdot5^3}=\dfrac{2^9\cdot3\cdot5^2\left(1+2^5\cdot3^9\right)}{-2^7\cdot3\cdot5^3\left(5+2^{11}\cdot3^{10}\right)}=-\dfrac{2^2\left(1+2^5\cdot3^9\right)}{5\left(5+2^{11}\cdot3^{10}\right)}\)
Đề tự chế???
![](https://rs.olm.vn/images/avt/0.png?1311)
\(=\dfrac{5^2\cdot6^{11}\cdot2^8+6^2\cdot6^6\cdot2^6\cdot15^2}{2\cdot6^{12}\cdot10^4-3^8\cdot2^{18}\cdot3^3\cdot5^3}\)
\(=\dfrac{5^2\cdot2^{19}\cdot3^{11}+3^8\cdot2^8\cdot2^6\cdot3^2\cdot5^2}{2^{13}\cdot3^{12}\cdot2^4\cdot5^4-3^{11}\cdot2^{18}\cdot5^3}\)
\(=\dfrac{5^2\cdot2^{19}\cdot3^{11}+3^{10}\cdot2^{14}\cdot5^2}{2^{17}\cdot3^{12}\cdot5^4-3^{11}\cdot2^{18}\cdot5^3}\)
\(=\dfrac{5^2\cdot2^{14}\cdot3^{10}\left(2^5\cdot3+1\right)}{2^{17}\cdot3^{11}\cdot5^3\left(3\cdot5-2\right)}\)
\(=\dfrac{1}{5}\cdot\dfrac{1}{8}\cdot\dfrac{1}{3}\cdot\dfrac{32\cdot3+1}{15-2}\)
\(=\dfrac{1}{120}\cdot\dfrac{97}{13}=\dfrac{97}{1560}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a ) \(5\left(x^2\right)+7x+2\)
\(\Leftrightarrow5x^2+7x+2=0\)
\(\Leftrightarrow5x^2+5x+2x+2=0\)
\(\Leftrightarrow\left(5x+2\right)\left(x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=-\dfrac{2}{5}\\x=-1\end{matrix}\right.\)
Vậy .............
b ) \(\dfrac{x+1}{17}+\dfrac{x+2}{16}=\dfrac{x+3}{15}+\dfrac{x+4}{14}\)
\(\Leftrightarrow\dfrac{x+1}{17}+1+\dfrac{x+2}{16}+1=\dfrac{x+3}{15}+1+\dfrac{x+4}{14}+1\)
\(\Leftrightarrow\dfrac{x+18}{17}+\dfrac{x+18}{16}=\dfrac{x+18}{15}+\dfrac{x+18}{14}\)
\(\Leftrightarrow\dfrac{x+18}{17}+\dfrac{x+18}{16}-\dfrac{x+18}{15}-\dfrac{x+18}{14}=0\)
\(\Leftrightarrow\left(x+18\right)\left(\dfrac{1}{17}+\dfrac{1}{16}-\dfrac{1}{15}-\dfrac{1}{14}\right)=0\)
Vì \(\left(\dfrac{1}{17}+\dfrac{1}{16}-\dfrac{1}{15}-\dfrac{1}{14}\right)\ne0\)
Ta có : \(x+18=0\Leftrightarrow x=-18\)
Vậy ......
c ) \(\dfrac{x-1}{x-3}=\dfrac{x-4}{x-7}\)
\(\Leftrightarrow\left(x-1\right)\left(x-7\right)=\left(x-3\right)\left(x-4\right)\)
\(\Leftrightarrow x^2-7x-x+7=x^2-4x-3x+12\)
\(\Leftrightarrow-x=5\)
\(\Leftrightarrow x=-5\)
Vậy ..
![](https://rs.olm.vn/images/avt/0.png?1311)
Câu 1:
\(S=\frac{10}{7}+\frac{10}{7^2}+\frac{10}{7^3}+...+\frac{10}{7^{10}}\)
\(\frac{1}{7}S=\frac{10}{7^2}+\frac{10}{7^3}+....+\frac{10}{7^{11}}\)
\(\rightarrow\)\(\left(1-\frac{1}{7}\right).S=\frac{10}{7}-\frac{10}{7^{11}}\)
=> \(S=\frac{10.7^{10}-10}{7^{10}.6}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 31 . 65 + 31 . 35 - 500
=31(65+35)-500
=31..100-500
=3100-500
=2600
Kết quả là 8423,9181